Implementasi Program Kampus Mengajar Angatan 6 Dalam Meningkatkan Kompetensi Literasi Dan Numerasi Peserta Didik - Hikami, Nuria; Shofyatun Nufusita, Wahida; Ibrahim, Malik; Akrom, Muhamad; Riana, Riana (KREASI : Jurnal Inovasi dan Pengabdian kepada Masyarakat, 2023)
One of the problems at SMPN 2 Batukliang Utara is the lack of literacy and numeracy. This is proven by education report cards which show that literacy and numeracy scores are still lacking. In reality, not all students are able to achieve the expected competencies. This inability to understand scientific concepts is caused by the difficulties faced by students in responding to the learning given, which has an impact on students' low literacy and numeracy skills. To overcome this problem, of course appropriate learning media is needed. Learning media is also an important part of the learning process, so it is necessary to look for creative learning media that allows students to understand the material. The presence of campus students teaching here can become partners for teachers in implementing innovation in learning, and learning models that are creative, innovative and fun. In this program, campus teaching students are responsible for assisting the school in the teaching and learning process, as well as school adaptation. Apart from that, students also have a responsibility to improve student literacy and numeracy. The results of this program are expected to increase the literacy and numeracy levels of students at SMP Negeri 2 Batukliang Utara.